RESPON KAUM PEREMPUAN DALAM MENYIKAPI KASUS PERCERAIAN AKIBAT PERSELINGKUHAN PERSPEKTIF HUKUM KELUARGA - Sitti Musyahidah; Rustina (Musawa: Journal for Gender Studies, 2023)
This study aims to determine the response of women in dealing with divorce due to infidelity to upholding family resilience. In this study, researchers focused on the problem of women's efforts in household resilience to the process of divorce due to infidelity. The results of this study indicate that women's response to divorce due to infidelity is family law, namely, women after divorce and living as single parents remain a priority for themselves and their children because the law never leaves individuals, because the law can be in the form of Maslahah with the meaning of maintenance of religion, soul, mind, lineage and property. Women who have become single parents as a result of divorce as a result of an affair, this is not to be ridiculed and must be avoided because things happen beyond a woman's reasoning, therefore these women still exist and remain whole women and appear as great women.